1997
DOI: 10.1159/000178005
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B<sub>6</sub> and Vitamin C Status in Elderly Patients with Infections during Hospitalization

Abstract: We have evaluated whether vitamin B6 and C metabolism may be altered by infection in the elderly. Vitamin B6 and C biochemical status has been assessed for times over a period of 21 days (days 0, 7, 14, and 21) in 18 subjects ≧75 years. The subjects were divided into 3 groups: group I (8 subjects with acute infection), group II (4 malnourished subjects), and group III (6 control subjects). Vitamin B6 status was determined by plasma pyridoxal-5’-phosphate (PLP) and erythrocyte a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 16 publications
3
21
0
Order By: Relevance
“…Ascorbate serves as an electron donor, transmitting hydrogen to various acceptors and thereby directly interfering with ROS (Frei et al, 1989). Through the regeneration of ␣-tocopherol, ascorbate can also indirectly contribute to the prevention of lipid peroxidation (Burton and Ingold, 1989), thus explaining why oxidative stress leads in vivo and in vitro to a rapid depletion of extracellular ascorbate (Mendiratta et al, 1998;Pfitzenmeyer et al, 1997). Transferrin as well as lactoferrin bind free Fe 2ϩ ions thus preventing their participation in generating hydroxyl radicals (Halliwell and Gutteridge, 1990).…”
Section: Extracellular Mechanismsmentioning
confidence: 99%
“…Ascorbate serves as an electron donor, transmitting hydrogen to various acceptors and thereby directly interfering with ROS (Frei et al, 1989). Through the regeneration of ␣-tocopherol, ascorbate can also indirectly contribute to the prevention of lipid peroxidation (Burton and Ingold, 1989), thus explaining why oxidative stress leads in vivo and in vitro to a rapid depletion of extracellular ascorbate (Mendiratta et al, 1998;Pfitzenmeyer et al, 1997). Transferrin as well as lactoferrin bind free Fe 2ϩ ions thus preventing their participation in generating hydroxyl radicals (Halliwell and Gutteridge, 1990).…”
Section: Extracellular Mechanismsmentioning
confidence: 99%
“…Increased free radical production and lipid peroxidation and decreased antioxidant capacity may occur during critical illness, the combination of which would result in multiple organ failure [4, 5]. Our previous studies [6, 7] and others [810] have reported lower and compromised vitamin B-6 status in hospitalized and critically ill patients. Stress, inflammation, and clinical conditions may increase the utilization and metabolic turnover of vitamin B-6 and lower its body pool.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (Potera et al, 1977;Vir & Love, 1978;Louw et al, 1992;Pfitzenmeyer et al, 1997) have reported lower vitamin B6 status in hospitalized patients. Potera et al (1977) reported that advanced breast cancer patients had significantly lower plasma PLP levels than healthy women of similar age.…”
Section: Introductionmentioning
confidence: 99%